Student's Expressive Speak With Teacher in Vocational High School - Pambudi, Findi Setya; Susanto, Gatut; Nurchasanah, Nurchasanah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study analyzes the expressive speech politeness of students and teachers at An-Nur Bululawang Vocational School, Malang Regency. This study aims to determine the form of expressive speech politeness and the function of students' expressive speech politeness toward teacher speech at school. This research was conducted using a qualitative approach. This type of research is a type of pragmatic research. The data in this study are in the form of speech between students and teachers in expressive politeness at school. The data source for this research was in the form of recordings of students' and teachers' speeches, which were then transcribed in written form. Data collection techniques in this study used observation and recording techniques. Data analysis in this study used the Miles and Huberman interactive model in general, covering three stages, namely (1) data collection, (2) data reduction, and (3) data presentation. The results of this study indicate that (1) the forms of expressive speech between students and the teacher, namely declarative speech forms, imperative speech forms, and interrogative speech forms, and (2) the function of expressive speech politeness between students and teachers, namely the politeness function of expressive speech pleasure, thank you, apologize, complain, greet, praise, tease, and tease. The use of expressive politeness between students and teachers at school is used relevantly according to the context, and this expressive speech can help students convey emotional feelings to the teacher so that in the learning process, they easily achieve learning goals and can motivate students' development while at school.